Low-refraction high-performance sealing glue for ar / vr glasses chip and preparation method thereof
Patent Information
- Application Number
- CN202610931732.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-06-26
AI Technical Summary
[0006]本发明解决的技术问题在于,现有AR/VR眼镜芯片用光学密封胶在降低折射率的同时,容易因含氟组分相容性不足、固化收缩或挥发性副产物释放而产生相分离、气泡、雾度升高及界面应力问题
1.本发明采用脂环族环氧树脂、酸酐固化剂与端羟基聚三氟丙基甲基硅氧烷配合形成固化体系,利用端羟基聚三氟丙基甲基硅氧烷中的三氟丙基侧基和硅氧烷链段降低固化胶膜的整体折射率,同时以脂环族环氧树脂开环固化作为主要网络形成方式,避免以丙烯酸酯自由基链式聚合作为主要固化路径,从而在获得低折射性能的同时降低固化体积收缩率,减小芯片与透镜密封界面处的残余应力。
Smart Images

Figure CN122465557B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optical packaging materials technology, and in particular to a low-refractive-index high-performance sealant for AR / VR glasses chips and its preparation method. Background Technology
[0002] Optical chips, microdisplay units, and lens assemblies in AR / VR glasses typically require fixation and encapsulation using transparent sealants. These sealants not only need to meet adhesion and protection requirements but also need to maintain high light transmittance, low haze, and a stable refractive index within a thin layer to minimize impact on the imaging optical path. As AR / VR display devices become thinner and higher resolution, the sealing gap between the chip and lens is further reduced, making issues with the sealant, such as curing shrinkage, interface stress, bubble defects, and light scattering, more likely to affect device reliability.
[0003] Among existing optical sealants, acrylate systems have a relatively fast curing speed and a large range of formulation adjustments. However, their free radical polymerization process is usually accompanied by significant volume shrinkage, which can easily form residual stress between rigid substrates such as chips, glass, or lenses, and may lead to a decrease in interfacial strength after thermal shock. Epoxy sealants have good adhesion and heat resistance, but ordinary epoxy systems have a relatively high refractive index, making it difficult to meet the low-refractive-index encapsulation requirements when directly used for sealing AR / VR optical chips.
[0004] To reduce the refractive index, existing technologies typically introduce low-refractive-index components such as fluorinated resins, fluorinated acrylates, or fluorinated siloxanes into sealants. However, fluorinated components have limited compatibility with polar components such as epoxy resins and anhydride curing agents, easily leading to phase separation or localized enrichment during curing. This results in discontinuous regions of refractive index within the sealant layer, consequently increasing haze and decreasing light transmittance. Some coordination catalysis or metal complexation promoting systems may also release low-boiling-point small molecules during curing. These components are difficult to expel within the confined encapsulation space and are prone to forming microbubbles or void defects during temperature curing, which also compromises optical uniformity.
[0005] Therefore, there is an urgent need to provide a low-refractive-index sealant suitable for AR / VR glasses chip packaging, which can improve the compatibility between fluorinated components and epoxy systems while reducing the refractive index, reducing volatile defects and volume shrinkage during the curing process, and maintaining good light transmittance, low haze and interface stability. Summary of the Invention
[0006] The technical problem solved by this invention is that existing optical sealants for AR / VR glasses chips, while reducing the refractive index, are prone to phase separation, bubbles, increased haze, and interfacial stress due to insufficient compatibility of fluorine-containing components, curing shrinkage, or release of volatile byproducts.
[0007] To address the above problems, the present invention provides the following technical solution: In a first aspect, the present invention provides a low-refractive-index high-performance sealant for AR / VR glasses chips, wherein the raw materials, by weight, include: 35-45 parts of alicyclic epoxy resin; 5-12 parts of acid anhydride curing agent; 1-3 parts of fluorinated alkyltrimethoxysilane; 40-50 parts of hydroxyl-terminated polytrifluoropropylmethylsiloxane; Aluminum acetylacetone 1.5–3 parts; 3 to 6 parts of bismaleimide compounds.
[0008] By employing the above technical solution, alicyclic epoxy resin and anhydride curing agent constitute the main curing matrix of the sealant. The alicyclic epoxy structure undergoes a ring-opening reaction under heating conditions and participates in the formation of the curing network together with the anhydride curing agent. Compared to the free radical addition polymerization of acrylate double bonds, this type of ring-opening curing process exhibits more gradual volume changes, which is beneficial for reducing residual curing stress at the interfaces of chips, lenses, and glass substrates.
[0009] Hydroxyl-terminated polytrifluoropropylmethylsiloxane contains a siloxane backbone and trifluoropropyl side groups. The trifluoropropyl side groups help reduce the refractive index of the cured film, and the siloxane segments possess a certain degree of flexibility, acting as stress buffers in the cured network. The silanol groups at the ends of the molecular chains can also undergo coordination exchange with aluminum acetylacetonate, allowing the fluorinated siloxane component to exist not only in a physically dispersed form in the system but also to participate in the coordination structure adjustment during the early stages of curing. This reduces the migration and phase separation tendency of the fluorinated siloxane component during the curing process.
[0010] Fluorinated alkyltrimethoxysilanes contain both fluorinated alkyl segments and trimethoxysilane end groups. The fluorinated alkyl segments and hydroxyl-terminated polytrifluoropropylmethylsiloxanes exhibit similar low surface energy characteristics, while the trimethoxysilane end groups can undergo hydrolytic condensation reactions with polar components in the system or hydroxyl groups on the substrate surface. When this component is located between the fluorinated siloxane phase and the epoxy continuous phase, it can improve the dispersion of both types of components and reduce the possibility of visible-scale phase separation structures forming during curing.
[0011] Aluminum acetylacetonate acts as both a coordination reaction component and a latent curing promoter in the system. During the initial heating phase of curing, the terminal silanol groups of hydroxyl-terminated polytrifluoropropylmethylsiloxane undergo coordination exchange with aluminum acetylacetonate, generating a siloxane-aluminum complex while releasing acetylacetonate ligands. This process, on the one hand, establishes a connection between the fluorosiloxane segments and the aluminum coordination centers, and on the other hand, provides aluminum coordination structures that can participate in promoting the subsequent epoxy ring-opening curing reaction.
[0012] Bismaleimide compounds contain maleimide double bonds. Influenced by the imide structure, these double bonds exhibit nucleophilic addition reactivity. The acetylacetone components released during the early curing stage contain reactive methylene groups, which, in the presence of an aluminum coordination structure, can undergo Michael addition reactions with the maleimide double bonds. Therefore, some low-boiling-point acetylacetone components can be converted into addition structures with higher molecular weights and lower volatility, thereby reducing their likelihood of escape during the subsequent temperature-curing stage.
[0013] As the temperature rises further, a significant proportion of the alicyclic epoxy resin in the system undergoes ring-opening transformation and forms a cross-linked network with the anhydride curing agent. At this point, the previously formed aluminosilicate coordination structure, bismaleimide addition structure, and fluorinated siloxane segments are all distributed in the cured system. Since the fixation process of volatile components occurs before the system viscosity increases significantly, the risk of low-boiling-point byproducts nucleating and forming bubbles in the adhesive layer is reduced. Simultaneously, the fluorinated siloxane components, after compatibility adjustment, are dispersed in the epoxy curing network, which also helps reduce light scattering caused by phase separation.
[0014] Therefore, the sealant of this invention, through the combination of alicyclic epoxy resin, anhydride curing agent, hydroxyl-terminated polytrifluoropropylmethylsiloxane, aluminum acetylacetonate, bismaleimide compounds, and fluorinated alkyltrimethoxysilane, enables low-refractive-index modification, compatibility adjustment, coordination exchange, volatile component capture, and epoxy ring-opening curing to occur synergistically within the same system. This formulation design is beneficial for reducing the refractive index of the cured adhesive film, minimizing phase separation and bubble defects, and improving the light transmittance, haze, volume shrinkage, and interfacial stability of the cured adhesive layer after thermal shock.
[0015] Preferably, the sealant comprises, by weight, the following raw materials: 40 parts of alicyclic epoxy resin; 8 parts of acid anhydride curing agent; 1 part of fluorinated alkyltrimethoxysilane; 45 parts of hydroxyl-terminated polytrifluoropropylmethylsiloxane; 2 parts of aluminum acetylacetonate; Four portions of bismaleimide compounds.
[0016] By adopting the above technical solution, the dosage relationship of alicyclic epoxy resin, acid anhydride curing agent, and hydroxyl-terminated polytrifluoropropylmethylsiloxane is suitable for forming a cured adhesive layer that combines transparency, low refractive index, and mechanical stability. When aluminum acetylacetonate and bismaleimide compounds are combined in the above dosage, they can provide the reaction components required for coordination exchange and volatile component capture, while minimizing the impact on adhesive uniformity and post-curing optical properties due to excessive capture agents or metal coordinating components.
[0017] Preferably, the alicyclic epoxy resin is 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate or bis(3,4-epoxycyclohexylmethyl)adipic acid ester; the anhydride curing agent is methylhexahydrophthalic anhydride or hexahydrophthalic anhydride; the fluorinated alkyl trimethoxysilane is tridecafluorooctyltrimethoxysilane or heptadecafluorodecyltrimethoxysilane; and the bismaleimide compound is N,N'-m-phenylenebismaleimide or 4,4'-diphenylmethanebismaleimide.
[0018] By adopting the above technical solutions, the aforementioned alicyclic epoxy resins all contain ring-opening curable alicyclic epoxy groups, which are suitable for forming transparent curing networks; methyl hexahydrophthalic anhydride and hexahydrophthalic anhydride have good curing compatibility with alicyclic epoxy resins, which helps to reduce the color and optical absorption of the cured system; tridecafluorooctyltrimethoxysilane and heptadecafluorodecyltrimethoxysilane can provide fluorinated segments and hydrolyzable silane end groups, which can be used to adjust the compatibility between fluorinated siloxane components and epoxy bodies; N,N'-m-phenylenebismaleimide and 4,4'-diphenylmethanebismaleimide both have two maleimide double bonds, which can participate in the addition fixation of acetylacetone components and further enter the cured network structure.
[0019] Preferably, the hydroxyl-terminated polytrifluoropropylmethylsiloxane has a dynamic viscosity of 1100–2900 mPa·s at 25°C.
[0020] By adopting the above technical solution, the dynamic viscosity of hydroxyl-terminated polytrifluoropropylmethylsiloxane is controlled within the aforementioned range, facilitating its dispersion in the epoxy system under high shear conditions and ensuring it has suitable segment length and hydroxyl-terminated content for coordination exchange. If the viscosity is too low, the contribution of the fluorosiloxane segments to low refractive index modification and stress buffering is limited; if the viscosity is too high, the difficulty of mixing, degassing, and subsequent sizing processes will increase, and it may also affect the uniformity of the adhesive.
[0021] Preferably, the hydroxyl-terminated polytrifluoropropylmethylsiloxane is prepared by the following steps: Under inert gas protection, the monomer of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane was heated to 80-100°C, and tetramethylammonium hydroxide and deionized water were added. The mixture was stirred at 80-100°C for 3-6 hours to carry out ring-opening polymerization. Then, the temperature was raised to 140-160°C and held for 1.5-2.5 hours to decompose and volatilize the tetramethylammonium hydroxide. Subsequently, under vacuum conditions of -0.090 to -0.098 MPa, the low molecular weight cyclic oligomers were removed at 140-160°C, and the mixture was cooled to room temperature to obtain hydroxyl-terminated polytrifluoropropylmethylsiloxane.
[0022] By employing the above technical solution, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane undergoes ring-opening polymerization in the presence of tetramethylammonium hydroxide and deionized water. Deionized water participates in the regulation of the chain-terminal hydroxyl structure, while tetramethylammonium hydroxide catalyzes the ring-opening of the cyclic siloxane. After the polymerization reaction, a temperature treatment decomposes the tetramethylammonium hydroxide and causes it to volatilize from the system, reducing the impact of residual catalyst on the storage stability of the sealant and subsequent curing reactions. After depressurization to remove low-molecular-weight cyclic oligomers, the resulting hydroxyl-terminated polytrifluoropropylmethylsiloxane is less prone to low-molecular-weight migration or volatilization during subsequent thermosetting, which helps maintain the optical uniformity of the adhesive layer.
[0023] Preferably, the material ratio used in preparing the hydroxyl-terminated polytrifluoropropylmethylsiloxane is: 100 parts by weight of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane monomer, combined with 0.05 to 0.08 parts by weight of tetramethylammonium hydroxide and 0.05 to 0.12 parts by weight of deionized water.
[0024] By employing the above technical solution, the amounts of tetramethylammonium hydroxide and deionized water affect the ring-opening polymerization rate, chain growth rate, and end-hydroxyl content. Controlling both within the aforementioned ranges helps to obtain end-hydroxyl polytrifluoropropylmethylsiloxanes with suitable dynamic viscosity and moderate end-hydroxyl reactivity. When this component is incorporated into the sealant system, it simultaneously provides a low-refractive-index fluorine-containing structure, flexible siloxane segments, and end-group reaction sites for coordination exchange with aluminum acetylacetonate.
[0025] Secondly, the present invention provides a method for preparing a low-refractive-index high-performance sealant for AR / VR glasses chips, comprising the following steps: S1. Under conditions of 20-25℃ and relative humidity below 30%, alicyclic epoxy resin and acid anhydride curing agent are added to a mixer, followed by the dropwise addition of fluorinated alkyl trimethoxysilane. The dispersion disc is then started to stir to obtain a basic homogeneous epoxy liquid. S2. Add hydroxyl-terminated polytrifluoropropylmethylsiloxane to the basic homogeneous epoxy liquid obtained in S1, adjust the stirrer to high-shear emulsification mode, and while dispersing under strong shear, add aluminum acetylacetonate and bismaleimide compounds in the form of solid powder in batches at a uniform rate to continuously disperse under high shear. S3. Seal the mixer and turn on the vacuum system. Switch the mixing mode to low-speed anchor scraping mixing to degas the mixture and obtain a homogeneous sealant liquid after degassing.
[0026] By adopting the above technical solution, the preparation process arranges the order of addition according to component compatibility and material state. Alicyclic epoxy resin and acid anhydride curing agent are first mixed to form a continuous phase. Fluorinated alkyl trimethoxysilane enters the system at this stage, allowing for initial dispersion before the subsequent addition of fluorinated siloxane components. Hydroxyl-terminated polytrifluoropropylmethylsiloxane is then emulsified under high shear and enters the epoxy continuous phase. Aluminum acetylacetonate and bismaleimide compounds are subsequently added in powder form in stages to reduce localized agglomeration. After mixing, low-speed vacuum degassing is performed to reduce air bubbles introduced during the high-shear process.
[0027] In S1, the alicyclic epoxy resin and acid anhydride curing agent first form a basic homogeneous epoxy liquid. The viscosity of the system is relatively low at this stage, suitable for the dispersion of fluorinated alkyltrimethoxysilanes. Adding the fluorinated alkyltrimethoxysilane before the hydroxyl-terminated polytrifluoropropylmethylsiloxane allows it to initially distribute within the continuous phase composed of epoxy resin and acid anhydride curing agent, making it easier to exert its interface-modulating effect when it subsequently contacts the fluorinated siloxane component. Temperature control at 20–25°C and relative humidity control at below 30% are primarily used to limit the excessively rapid hydrolysis and condensation of the silane component in the initial mixing stage, reducing the risk of abnormal viscosity increases or localized condensate formation during the premixing stage.
[0028] In step S2, after the hydroxyl-terminated polytrifluoropropylmethylsiloxane is added to the basic homogeneous epoxy liquid, it needs to be dispersed in the continuous epoxy phase using high-shear emulsification. This fluorosiloxane component differs from the alicyclic epoxy system in terms of polarity and surface energy, and is prone to localized enrichment under normal low-speed stirring. High-shear emulsification can reduce the size of the dispersed phase, allowing the adhesive to maintain a more uniform dispersion before curing. At this point, the previously added fluoroalkyltrimethoxysilane is located between the fluorosiloxane component and the continuous epoxy phase, reducing the tendency for interfacial incompatibility between the two types of components.
[0029] Aluminum acetylacetonate and bismaleimide compounds are added in stages at a uniform rate in solid powder form. This aims to reduce the instantaneous amount of powder added and prevent rapid accumulation of powder in localized areas. Aluminum acetylacetonate subsequently undergoes coordination exchange with hydroxyl-terminated polytrifluoropropylmethylsiloxane and participates in the curing process of the alicyclic epoxy resin; the bismaleimide compounds need to contact the acetylacetonate components that may be released during the early stages of curing, thereby participating in the addition fixation reaction. Adding both types of powders in stages under high shear conditions improves their wetting and dispersion, reducing the impact of undispersed particles on the transparency and curing uniformity of the adhesive.
[0030] In S3, the premixed adhesive undergoes vacuum degassing. High-shear dispersion is beneficial for emulsification and powder dispersion, but it also introduces a certain amount of fine air bubbles. If these bubbles remain in the adhesive, they can easily form voids or scattering defects during subsequent application and thermosetting. Switching the stirring mode to low-speed anchor-type wall-scraping agitation allows the adhesive to slowly tumble in a vacuum environment, promoting the escape of entrained gases while avoiding further excessive shearing. Wall-scraping agitation also reduces the retention of the adhesive on the container walls and bottom, resulting in a more uniform degassing process.
[0031] The key to this preparation method lies in the coordination of the addition sequence, shear state, and degassing conditions. Fluoroalkyltrimethoxysilane is introduced first into the epoxy continuous phase, facilitating subsequent compatibility adjustment; hydroxyl-terminated polytrifluoropropylmethylsiloxane is dispersed under high shear, reducing the risk of phase separation before curing; aluminum acetylacetonate and bismaleimide compounds are added in stages to ensure a more uniform distribution of coordination exchange and trapping components in the adhesive; low-speed vacuum degassing reduces residual gas within the adhesive. The resulting sealant is suitable for subsequent dispensing, bonding, and stepped temperature curing.
[0032] Preferably, in step S1, the stirring speed of the dispersion disc is set to 400-600 rpm, and the stirring time is 15-25 minutes.
[0033] By employing the above technical solution and stirring at 400–600 rpm for 15–25 minutes, a relatively homogeneous basic mixture system can be formed from the alicyclic epoxy resin, acid anhydride curing agent, and fluorinated alkyl trimethoxysilane. Insufficient stirring intensity or too short a stirring time will result in inadequate distribution of the silane component in the basic system; excessively high stirring speed or too long a stirring time may increase air entrainment and increase the burden on subsequent degassing. These conditions, combined with the subsequent high-shear emulsification step, are suitable for forming a stable premixed base liquid.
[0034] Preferably, in step S2, the rotation speed of the high-shear emulsification mode is set to 1500-2000 rpm, and the high-shear dispersion time is 40-50 minutes; aluminum acetylacetonate and bismaleimide compound powders are added uniformly in 3-5 batches.
[0035] By adopting the above technical solution, a shear condition of 1500–2000 rpm can meet the emulsification and dispersion requirements of hydroxyl-terminated polytrifluoropropylmethylsiloxane, and also helps to wet the aluminum acetylacetonate and bismaleimide compound powders. Controlling the dispersion time to 40–50 minutes ensures thorough mixing of the fluorosiloxane component and the powder component, while avoiding excessive temperature rise in the system due to prolonged high shear. Adding the powder in 3–5 portions prevents excessively high local powder concentrations in the system, thus improving the uniformity of the subsequent curing reaction.
[0036] Preferably, in step S3, the vacuum system evacuates the machine to a gauge pressure of -0.090 to -0.098 MPa, the speed of the low-speed anchor-type wall scraper is set to 30 to 50 rpm, and the degassing treatment time is 30 to 45 minutes.
[0037] By adopting the above technical solution, a vacuum condition with a gauge pressure of -0.090 to -0.098 MPa can promote the escape of entrained gas in the adhesive. Controlling the rotation speed of the low-speed anchor-type wall-scraping agitator at 30–50 rpm maintains a slow flow of the adhesive, preventing the re-entry of air. When the degassing time is 30–45 minutes, visible air bubbles and some fine air bubbles in the adhesive can be sufficiently eliminated, resulting in a homogeneous sealant with a lower risk of void defects during subsequent application and heat curing.
[0038] In summary, the present invention has at least one of the following beneficial technical effects: 1. This invention uses an alicyclic epoxy resin, an anhydride curing agent, and hydroxyl-terminated polytrifluoropropylmethylsiloxane to form a curing system. The trifluoropropyl side groups and siloxane segments in the hydroxyl-terminated polytrifluoropropylmethylsiloxane reduce the overall refractive index of the cured film. At the same time, the ring-opening curing of the alicyclic epoxy resin is used as the main network formation method, avoiding the use of acrylate free radical chain polymerization as the main curing path. This results in low refractive properties while reducing the curing volume shrinkage rate and decreasing the residual stress at the chip-lens sealing interface.
[0039] 2. In this invention, a fluorinated alkyl trimethoxysilane is added to the system. The fluorinated alkyl segments in this component can form a compatibility relationship with hydroxyl-terminated polytrifluoropropylmethylsiloxane, and its trimethoxysilane end groups can interact with the epoxy continuous phase and the surface of silicon and glass substrates. This improves the dispersion state of the fluorinated siloxane component in the epoxy system, reduces the risk of visible light-scale phase separation structure during curing, and further reduces light scattering caused by the discontinuity of refractive index inside the adhesive layer, improves the transmittance of the cured adhesive film, and reduces haze.
[0040] 3. This invention utilizes the coordination exchange between aluminum acetylacetonate and the terminal silanol groups of hydroxyl-terminated polytrifluoropropylmethylsiloxane to form a coordination compound containing an aluminum silicate structure during the early stage of curing. Simultaneously, the maleimide double bond in the bismaleimide compound can undergo an addition reaction with the low-boiling-point acetylacetonate component generated during the coordination exchange process, transforming this low-boiling-point component into a less volatile addition structure. This reduces the possibility of volatile byproducts escaping during temperature curing and minimizes air bubbles or voids within the adhesive layer.
[0041] 4. The preparation method of this invention proceeds in the following order: premixing of the epoxy continuous phase, high-shear emulsification of fluorinated siloxanes, phased addition of aluminum acetylacetonate and bismaleimide compounds, and low-speed vacuum degassing. This ensures a relatively uniform distribution of the compatibility adjustment component, fluorinated siloxane component, coordination reaction component, and trapping reaction component in the adhesive solution, and reduces residual air bubbles introduced during mixing. The resulting homogeneous sealant solution is suitable for subsequent micro-dispensing and programmed temperature curing, which is beneficial for obtaining an AR / VR glasses chip sealant layer with low refractive index, high light transmittance, low haze, low water vapor transmission rate, and good interfacial stability after thermal shock. Attached Figure Description
[0042] Figure 1 The Fourier transform infrared spectra of Embodiment 1 of the present invention at different curing stages; Figure 2 This is a differential scanning calorimetry curve of the vacuum degassing sealant liquid in Embodiment 1 of the present invention during the programmed temperature control process; Figure 3 The graphs show the thermogravimetric-escape gas coupled infrared spectroscopy (TGA) test results of Example 1 and Comparative Example 2 during the programmed curing process of this invention, where (a) is the mass retention curve and (b) is the mass retention curve at 1620 cm⁻¹. -1 Infrared absorbance curve of the gas escaping from the point. Detailed Implementation
[0043] The present invention will be further described in detail below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Modifications or substitutions made to the methods, steps, or conditions of the present invention without departing from the spirit and substance of the invention are all within the protection scope of the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0044] The names, CAS numbers and specifications of the main raw materials and reagents used in the following examples and comparative examples are as follows. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0045] 1,3,5-Trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, CAS No. 2374-14-3.
[0046] Tetramethylammonium hydroxide, CAS number 75-59-2.
[0047] Hydroxyl-terminated polytrifluoropropylmethylsiloxane, prepared by Examples 1 to 3 below, has a main chain repeating unit of -[Si(CH3)(CH2CH2CF3)-O]-, and both ends of the polymer chain are capped with -Si(CH3)(CH2CH2CF3)OH structures, resulting in a linear homopolymer. According to the control of the preparation process in this invention, its weight-average molecular weight is 15,000 to 40,000, and its molecular weight distribution index is 1.5 to 2.0.
[0048] 3,4-Epoxycyclohexylmethyl-3,4-Epoxycyclohexylcarboxylate, CAS No. 2386-87-0, has an epoxy equivalent of 131-143 g / eq and a dynamic viscosity of 350-450 mPa·s under test conditions at 25°C.
[0049] Methylhexahydrophthalic anhydride, CAS number 25550-51-0, has an anhydride equivalent of 168 g / eq.
[0050] Aluminum acetylacetonate, CAS number 13963-57-0.
[0051] N,N'-m-phenylenebismaleimide, CAS number 3006-93-7.
[0052] Tridecafluorooctyltrimethoxysilane, CAS number 85857-16-5.
[0053] Bis(3,4-epoxycyclohexylmethyl) adipate, CAS number 3130-19-6.
[0054] Hexahydrophthalic anhydride, CAS number 85-42-7.
[0055] Heptadecafluorodecyltrimethoxysilane, CAS No. 83048-65-1.
[0056] 4,4'-Diphenylmethane bismaleimide, CAS number 13676-54-5.
[0057] 1H,1H,2H,2H-perfluorooctyl acrylate, also known as tridecylfluorooctyl acrylate, CAS number 17527-29-6.
[0058] Dicumyl peroxide, CAS number 80-43-3.
[0059] Preparation Example 1: This preparation example provides a method for preparing hydroxyl-terminated polytrifluoropropylmethylsiloxane, including the following steps: (1) In a four-necked flask equipped with reflux condenser and nitrogen protection, 100 g of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane monomer was added, the temperature was raised to 90 °C, and then 0.08 g of tetramethylammonium hydroxide and 0.12 g of deionized water were added; the ring-opening polymerization was carried out by stirring at 90 °C for 3 hours. (2) Heat the system to 150°C and keep it at that temperature for 2 hours to allow the catalyst tetramethylammonium hydroxide to decompose and volatilize; (3) Subsequently, the low molecular weight cyclic oligomers were removed under reduced pressure at 150°C for 2 hours under vacuum pressure of -0.095 MPa. (4) After cooling to room temperature, a hydroxyl-terminated polytrifluoropropylmethylsiloxane product was obtained, and its dynamic viscosity at 25°C was tested to be 1100 mPa·s.
[0060] Preparation Example 2: This preparation example provides a method for preparing hydroxyl-terminated polytrifluoropropylmethylsiloxane, including the following steps: (1) In a four-necked flask equipped with reflux condenser and nitrogen protection, 100 g of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane monomer was added, the temperature was raised to 90 °C, and then 0.06 g of tetramethylammonium hydroxide and 0.08 g of deionized water were added; the ring-opening polymerization was carried out by stirring at 90 °C for 4.5 hours. (2) Heat the system to 150°C and keep it at that temperature for 2 hours to allow the catalyst tetramethylammonium hydroxide to decompose and volatilize; (3) Subsequently, the low molecular weight cyclic oligomers were removed under reduced pressure at 150°C for 2 hours under vacuum pressure of -0.095 MPa. (4) After cooling to room temperature, a hydroxyl-terminated polytrifluoropropylmethylsiloxane product was obtained, and its dynamic viscosity at 25°C was tested to be 1900 mPa·s.
[0061] Preparation Example 3: This preparation example provides a method for preparing hydroxyl-terminated polytrifluoropropylmethylsiloxane, including the following steps: (1) In a four-necked flask equipped with reflux condenser and nitrogen protection, 100 g of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane monomer was added, the temperature was raised to 90 °C, and then 0.05 g of tetramethylammonium hydroxide and 0.05 g of deionized water were added; the ring-opening polymerization was carried out by stirring at 90 °C for 6 hours. (2) Heat the system to 150°C and keep it at that temperature for 2 hours to allow the catalyst tetramethylammonium hydroxide to decompose and volatilize; (3) Subsequently, the low molecular weight cyclic oligomers were removed under reduced pressure at 150°C for 2 hours under vacuum pressure of -0.095 MPa. (4) After cooling to room temperature, a hydroxyl-terminated polytrifluoropropylmethylsiloxane product was obtained, and its dynamic viscosity at 25°C was tested to be 2900 mPa·s.
[0062] Example 1: This embodiment provides a method for preparing a low-refractive-index high-performance sealant for AR / VR glasses chips, including the following steps: (1) Under the conditions of 25°C and relative humidity below 30%, 40 parts by weight of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarbamate and 8 parts by weight of methylhexahydrophthalic anhydride were added to a double planetary mixer, and then 1 part by weight of tridecafluorooctyltrimethoxysilane was added dropwise. The dispersion disk was started and stirred continuously at 500 rpm for 20 minutes to obtain a basic homogeneous epoxy liquid. (2) Add 45 parts by weight of the hydroxyl-terminated polytrifluoropropylmethylsiloxane obtained in Preparation Example 2 to the mixer, adjust the equipment to high shear emulsification mode, set the speed to 1800 rpm, and while dispersing under strong shear, add 2 parts by weight of aluminum acetylacetonate and 4 parts by weight of N,N'-m-phenylenebismaleimide in solid powder form in 4 portions at a uniform speed, and continue high shear dispersion for 45 minutes. (3) Seal the mixer, turn on the vacuum system, evacuate the machine to the gauge pressure -0.095MPa, switch the mixing mode to low speed anchor scraping mixing, set the speed to 40rpm, degas for 40 minutes, and obtain a homogeneous sealant liquid with no obvious bubbles visible. (4) Apply the degassed sealant to the area to be sealed of the AR / VR optical chip using a micro-dispensing machine at 25°C and complete the lens bonding. (5) Place the bonded device into a hot air circulating program oven and heat it from room temperature to 75°C at a heating rate of 2°C / min. Maintain the temperature for 50 minutes, then continue to heat it to 120°C at a heating rate of 2°C / min. Maintain the temperature for 100 minutes, and finally let it cool naturally to room temperature with the oven.
[0063] Example 2: This embodiment provides a method for preparing a low-refractive-index high-performance sealant for AR / VR glasses chips, including the following steps: (1) Under the conditions of 20℃ and relative humidity below 30%, 35 parts by weight of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and 5 parts by weight of methylhexahydrophthalic anhydride were added to a double planetary mixer, and then 1 part by weight of tridecafluorooctyltrimethoxysilane was added dropwise. The dispersion disk was started and stirred continuously at 400 rpm for 15 minutes to obtain a basic homogeneous epoxy liquid. (2) Add 40 parts by weight of the hydroxyl-terminated polytrifluoropropylmethylsiloxane obtained in Preparation Example 1 to the mixer, adjust the equipment to high shear emulsification mode, set the speed to 1500 rpm, and while dispersing under strong shear, add 1.5 parts by weight of aluminum acetylacetonate and 3 parts by weight of N,N'-m-phenylenebismaleimide in solid powder form in three uniform portions, and continue high shear dispersion for 40 minutes. (3) Seal the mixer, turn on the vacuum system, evacuate the machine to the gauge pressure -0.095MPa, switch the mixing mode to low speed anchor scraping mixing, set the speed to 30rpm, degas for 30 minutes, and obtain a homogeneous sealant liquid with no obvious bubbles visible. (4) Apply the degassed sealant to the area to be sealed of the AR / VR optical chip using a micro-dispensing machine at 25°C and complete the lens bonding. (5) Place the bonded device into a hot air circulating program oven and heat it from room temperature to 70°C at a heating rate of 1°C / min. Maintain the temperature for 40 minutes, then continue heating it to 115°C at a heating rate of 1°C / min. Maintain the temperature for 90 minutes, and finally let it cool naturally to room temperature with the oven.
[0064] Example 3: This embodiment provides a method for preparing a low-refractive-index high-performance sealant for AR / VR glasses chips, including the following steps: (1) Under the conditions of 25°C and relative humidity below 30%, 45 parts by weight of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and 12 parts by weight of methylhexahydrophthalic anhydride were added to a double planetary mixer, followed by the addition of 3 parts by weight of tridecafluorooctyltrimethoxysilane. The dispersion disk was started and stirred continuously at 600 rpm for 25 minutes to obtain a basic homogeneous epoxy liquid. (2) Add 50 parts by weight of the hydroxyl-terminated polytrifluoropropylmethylsiloxane obtained in Preparation Example 3 to the mixer, adjust the equipment to high shear emulsification mode, set the speed to 2000 rpm, and while dispersing under strong shear, add 3 parts by weight of aluminum acetylacetonate and 6 parts by weight of N,N'-m-phenylenebismaleimide in solid powder form in 5 portions at a uniform speed, and continue high shear dispersion for 50 minutes. (3) Seal the mixer, turn on the vacuum system, evacuate the machine to the gauge pressure -0.095MPa, switch the mixing mode to low speed anchor scraping mixing, set the speed to 50rpm, degas for 45 minutes, and obtain a homogeneous sealant liquid with no obvious bubbles visible. (4) Apply the degassed sealant to the area to be sealed of the AR / VR optical chip using a micro-dispensing machine at 25°C and complete the lens bonding. (5) Place the bonded device into a hot air circulating program oven and heat it from room temperature to 80°C at a heating rate of 2°C / min. Maintain the temperature for 60 minutes, then continue to heat it to 125°C at a heating rate of 2°C / min. Maintain the temperature for 120 minutes, and finally let it cool naturally to room temperature with the oven.
[0065] Example 4: This embodiment provides a method for preparing a low-refractive-index high-performance sealant for AR / VR glasses chips, including the following steps: (1) Under the conditions of 25°C and relative humidity below 30%, 40 parts by weight of bis(3,4-epoxycyclohexylmethyl) adipate and 8 parts by weight of hexahydrophthalic anhydride were added to a double planetary mixer, followed by 1 part by weight of heptadecafluorodecyltrimethoxysilane. The dispersion disk was started and stirred continuously at 500 rpm for 20 minutes to obtain a basic homogeneous epoxy liquid. (2) Add 45 parts by weight of the hydroxyl-terminated polytrifluoropropylmethylsiloxane obtained in Preparation Example 2 to the mixer, adjust the equipment to high shear emulsification mode, set the speed to 1800 rpm, and while dispersing under strong shear, add 2 parts by weight of aluminum acetylacetonate and 4 parts by weight of 4,4'-diphenylmethane bismaleimide in solid powder form in 4 portions at a uniform speed, and continue high shear dispersion for 45 minutes. (3) Seal the mixer, turn on the vacuum system, evacuate the machine to the gauge pressure -0.095MPa, switch the mixing mode to low speed anchor scraping mixing, set the speed to 40rpm, degas for 40 minutes, and obtain a homogeneous sealant liquid with no obvious bubbles visible. (4) Apply the degassed sealant to the area to be sealed of the AR / VR optical chip using a micro-dispensing machine at 25°C and complete the lens bonding. (5) Place the bonded device into a hot air circulating program oven and heat it from room temperature to 75°C at a heating rate of 2°C / min. Maintain the temperature for 50 minutes, then continue to heat it to 120°C at a heating rate of 2°C / min. Maintain the temperature for 100 minutes, and finally let it cool naturally to room temperature with the oven.
[0066] Comparative Example 1: Compared with Example 1, the only difference is that 45 parts by weight of 1H,1H,2H,2H-perfluorooctyl acrylate is used instead of 45 parts by weight of hydroxyl-terminated polytrifluoropropylmethylsiloxane; aluminum acetylacetonate and N,N'-m-phenylenebismaleimide are not added, but 2 parts by weight of dicumyl peroxide is added as a thermal initiator, and 4 parts by weight of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarbamate are added to keep the total amount of the system unchanged. The amounts of other raw materials and the preparation process are the same as in Example 1.
[0067] Comparative Example 2: Compared with Example 1, the only difference is that N,N'-m-phenylenebismaleimide is not added, and 4 parts by weight of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarbamate are added to keep the total amount of the system unchanged. The amounts of other raw materials and the preparation process are the same as in Example 1.
[0068] Comparative Example 3: Compared with Example 1, the only difference is that: tridecafluorooctyltrimethoxysilane is not added, and 1 part by weight of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate is added to keep the total amount of the system unchanged. The amounts of other raw materials and the preparation process are the same as in Example 1.
[0069] Comparative Example 4: Compared with Example 1, the only difference is that the first-stage stepped curing process is cancelled, and the bonded device is directly placed in a 120°C oven for constant temperature curing for 150 minutes. The remaining raw material usage, preparation process and cooling method are the same as in Example 1.
[0070] Test Example 1: The experimental steps are as follows: (1) Samples from three stages of the preparation process in Example 1 were taken as test objects, including: a homogeneous sealant sample before oven curing, a first-stage semi-cured sample obtained after being kept at 75°C for 50 minutes, and a final cured sample after being kept at 120°C for 100 minutes and cooled to room temperature.
[0071] (2) The above samples were tested using a Fourier transform infrared spectrometer equipped with an attenuated total reflectance accessory. The test scanning range was 4000 cm⁻¹. -1 ~500cm -1 The resolution is 4cm. -1 The number of scans was 32.
[0072] (3) Collect the air background spectrum and perform baseline calibration before testing. During testing, place the samples of each stage evenly on the diamond crystal surface of the attenuated total reflection accessory to ensure full contact between the sample and the crystal surface and avoid obvious bubble inclusions.
[0073] (4) After collecting the infrared absorption spectra of each sample, baseline correction and smoothing were performed on the obtained spectra, and the 3352 cm⁻¹ value was extracted. -1 3096cm -1 and 914cm -1 The relative absorbance of nearby characteristic absorption peaks. To reduce the influence of sample thickness and attenuated total internal reflection contact state on the test results, the absorbance of each characteristic peak was normalized after baseline correction, using the relatively stable Si-C or CF characteristic absorption peaks as internal standards.
[0074] The experimental results are shown in Table 1 and Figure 1 As shown.
[0075] Table 1. Record of infrared absorbance data of specific functional groups in samples at each stage of Example 1: According to Table 1 and Figure 1 It can be seen that after the first stage of curing, 3352cm -1 The intensity of the absorption peak associated with the silanol group in the vicinity decreases significantly, at 3096 cm⁻¹. -1 The intensity of the absorption peaks associated with the maleimide double bond also decreased synchronously; while the intensity of the peak at 914 cm⁻¹ also decreased. -1 The absorption peaks associated with alicyclic epoxy groups in the vicinity remained at a high level. These changes indicate that, during the isothermal stage at 75°C, the terminal hydroxyl polytrifluoropropylmethylsiloxane end group and the maleimide double bond-related structure may have participated in the early reactions in the system, while the alicyclic epoxy groups had not yet been largely consumed during this stage.
[0076] Furthermore, after the second stage of curing and cooling, 914cm -1 The significant decrease in the characteristic absorption peaks of nearby alicyclic epoxy groups indicates that the alicyclic epoxy groups underwent a significant transformation during the higher-temperature curing stage. (Combined with 3352 cm⁻¹) -1 and 3096cm -1 The phased changes in the absorption peak indicate that the system of this invention exhibits a trend of first undergoing terminal hydroxyl-related reactions and maleimide double bond-related reactions during programmed temperature curing, followed by alicyclic epoxy group conversion. This result is consistent with the stepwise reaction process of this application.
[0077] Test Example 2: The experimental steps are as follows: (1) Take about 12.4 mg of the homogeneous sealant liquid that has been vacuum degassing and has not yet undergone dispensing and heat curing in Example 1 as the test object, place it in a standard aluminum liquid sample crucible and seal it; take another empty aluminum crucible of the same specification, seal it with a pressure cap and use it as the reference end.
[0078] (2) Place the sample crucible and the reference crucible in the heating furnace of the differential scanning calorimeter and introduce high-purity nitrogen gas with a flow rate of 50 mL / min as a purging protective gas.
[0079] (3) Set the temperature control conditions corresponding to the thermosetting process in Example 1: raise the temperature from 25°C to 75°C at a heating rate of 2°C / min, and keep it at 75°C for 50 minutes; then continue to raise the temperature to 120°C at a heating rate of 2°C / min, and keep it at 120°C for 100 minutes.
[0080] (4) Start the test and record the heat flow changes of the sample during the programmed temperature control process. After the test, perform baseline correction and smoothing on the obtained heat flow curve, and perform integral analysis on the heat release signal that appears, and record the start time, peak time, corresponding real-time temperature and stage heat release enthalpy of each heat release stage.
[0081] The experimental results are shown in Table 2 and Figure 2 As shown.
[0082] Table 2. Characteristic data of vacuum degassing sealant liquid tested by programmable temperature differential scanning calorimetry in Example 1: According to Table 2 and Figure 2 Based on the data, under the programmed temperature control conditions used in Example 1, two relatively independent exothermic phases can be observed in the sample heat flow curve. The first exothermic signal begins at 21.6 min, corresponding to a real-time temperature of 68.2 °C; its peak occurs at 32.4 min, i.e., within the 75 °C isothermal phase, and the exothermic enthalpy of this phase is 18.35 J / g. Combined with the 3352 cm⁻¹ data from Test Example 1... -1 and 3096cm -1 The change in the absorption peak at this stage suggests that the exothermic reaction in this phase may be related to the terminal hydroxyl group-related reaction, changes in the coordination environment of the aluminum complex, and the maleimide double bond-related reaction. Because the exothermic enthalpy in this stage is relatively low, and in Test Example 1 it was 914 cm⁻¹ -1 The absorption peaks of nearby epoxy groups remain at a high level, indicating that this stage has not yet been dominated by a large proportion of alicyclic epoxy groups undergoing ring-opening curing.
[0083] The second stage of exothermic signal begins at 85.8 min, corresponding to a real-time temperature of 96.6℃; its peak occurs at 104.7 min, during the isothermal phase at 120℃, with an exothermic enthalpy of 247.12 J / g. This exothermic enthalpy is significantly higher than that of the first stage, which, combined with the final solidified material of 914 cm³ in Test Example 1, suggests otherwise. -1 The significant decrease in the absorption peak of nearby epoxy groups indicates that the alicyclic epoxy groups underwent a significant transformation at higher temperatures, forming a further cured cross-linked structure.
[0084] The above results indicate that the sealant of Example 1 exhibits a process characteristic of weak exothermic reaction at low temperatures and strong exothermic reaction at high temperatures under the set stepped heating conditions. This thermal analysis result is consistent with the stepped curing design in this application, which involves initial coordination / capture reactions followed by epoxy ring-opening curing.
[0085] Test Example 3: The experimental steps are as follows: (1) The vacuum degassing sealant prepared in Example 1 and the vacuum degassing sealant prepared in Comparative Example 2 were used as test objects. Approximately 15.2 mg of liquid sealant sample was weighed and placed in an alumina micro ceramic crucible.
[0086] (2) Place the crucible containing the sample into the heating furnace of the thermogravimetric analyzer, and introduce high-purity helium gas at a flow rate of 60 mL / min as the carrier gas and purge gas. The gas outlet of the thermogravimetric analyzer is connected to the isothermal gas cell of the Fourier transform infrared spectrometer through a polytetrafluoroethylene transmission line heated to 200 °C to reduce the condensation effect of volatile components during transmission.
[0087] (3) Set the temperature program conditions in the thermogravimetric analyzer corresponding to the curing process in Example 1: start from 25°C, raise the temperature to 75°C at a rate of 2°C / min, and hold at 75°C for 50 minutes; then continue to raise the temperature to 120°C at a rate of 2°C / min, and hold at 120°C for 100 minutes.
[0088] (4) After starting the program, the changes in sample mass over time and temperature are recorded synchronously; at the same time, the Fourier transform infrared spectrometer continuously scans the escaping gas entering the gas cell at a scan interval of 15 seconds / time, and extracts 1620 cm⁻¹. -1 The carbonyl-related absorption signal in the vicinity serves as a characteristic reference signal for acetylacetone-like volatile components.
[0089] The experimental results are shown in Table 3 and Figure 3 As shown.
[0090] Table 3. Thermogravimetric and infrared absorbance data of escaped gases during the curing process of Example 1 and Comparative Example 2: According to Table 3 and Figure 3 It can be seen that Comparative Example 2 exhibits a significant decrease in mass during the first stage of heating and the isothermal process at 75℃, while the mass at 1620cm³ is significantly reduced. -1 The infrared absorption signal of the nearby escaping gas was significantly enhanced. This result indicates that, without the addition of N,N'-m-phenylenebismaleimide, acetylacetone-like volatile components generated by processes such as coordination exchange are more likely to escape with the carrier gas, leading to a decrease in sample mass retention. These volatile components may increase the risk of bubble or void defect formation in confined packaging spaces.
[0091] In contrast, Example 1 maintained a quality retention rate of over 99.71% throughout the entire curing process, at 1620cm. -1The absorption signal of the nearby escaping gas remained at a low level. This result indicates that the escape of volatile byproducts in the system was significantly suppressed after the addition of the bismaleimide-based trapping component. Combining the results of Test Example 1 and Test Example 2, it can be inferred that during the first-stage curing process, the acetylacetone-based component may react with the maleimide double bond-related structure to transform into a low-volatility or non-volatile structure, thereby reducing the amount of gas released during the subsequent heating process.
[0092] The above thermogravimetric and volatile gas infrared spectroscopy test results show that the formulation of this application has low mass loss and weak volatile gas release signal during the programmed step curing process, which is consistent with the design concept of in-situ capture of volatile byproducts.
[0093] Test Example 4: The experimental steps are as follows: (1) The sealant solutions prepared in Examples 1-4 and Comparative Examples 2-4 and subjected to vacuum degassing were extracted as test materials. Each sealant solution was applied to a standard optical quartz glass substrate that had been pre-treated by plasma cleaning using a micro-precision dispensing device. A second piece of quartz glass of the same specifications was then covered, and the thickness of the internal adhesive layer was controlled by peripheral clamps and a 100-micron-thick polyimide film gasket.
[0094] (2) The clamped sample, together with the quartz glass fixture, is placed in a programmable temperature oven and heat-cured according to the temperature steps and time parameters recorded in the corresponding embodiment or comparative example. After curing is completed and the sample is cooled to room temperature in the oven, the cured adhesive film test assembly is obtained.
[0095] (3) The above test components were optically scanned using a UV-Vis spectrophotometer. The test wavelength range was set to 400nm~700nm. The instrument used air as a reference and deducted the optical attenuation of the blank double-layer quartz glass components of the same thickness and structure to obtain the integrated average transmittance of each sample in the visible light band.
[0096] (4) Transfer the test components to the test chamber of the haze tester equipped with an integrating sphere, and determine the ratio of the scattered light flux that deviates more than 2.5 degrees from the incident light direction after passing through the sample to the total transmitted light flux in accordance with the standard specifications. Randomly test each sample in five different areas on the surface, record and calculate the arithmetic mean of the haze.
[0097] (5) Apply each group of sealant liquid to a flat glass mold that has undergone demolding treatment, and heat-cure it according to its corresponding curing procedure. After curing and cooling to room temperature, peel it off to obtain an unsupported cured film with a thickness of 50±2 micrometers. Use an Abbe refractometer or ellipsometer to test the refractive index of each cured film at 25℃ and 589nm wavelength. For comparative samples with obvious haze or phase separation, record their apparent refractive index as a reference value. Test no less than 3 parallel samples for each group of samples, record and calculate the average refractive index.
[0098] The experimental results are shown in Table 4.
[0099] Table 4. Test data of optical properties of cured adhesive films in each embodiment and comparative example: According to the data in Table 4, the average transmittance of the cured films obtained in Examples 1-4 in the visible light band of 400nm-700nm is all higher than 98.80%, and the haze is all lower than 0.50%, indicating that the samples of each example have high visible light transmittance and low light scattering level under the test conditions. Meanwhile, the refractive index of Examples 1-4 is all lower than 1.42, indicating that the introduction of hydroxyl-terminated polytrifluoropropylmethylsiloxane and fluorinated alkylsilane components into the formulation system is beneficial to reducing the overall refractive index of the cured film.
[0100] Comparative Example 2, without the addition of N,N'-m-phenylenebismaleimide, exhibited an average transmittance of 93.42% and a haze of 8.76% in its cured film. Compared to Example 1, although Comparative Example 2 still contained hydroxyl-terminated polytrifluoropropylmethylsiloxane and maintained a relatively low refractive index, its haze significantly increased and its transmittance decreased. These results indicate that without the addition of bismaleimide-based trapping components, low-boiling-point byproducts that may be generated during coordination exchange are difficult to fully convert or fix in the early stages of curing, leading to the formation of bubbles or micro-defects in the cured adhesive layer, thereby increasing light scattering.
[0101] Comparative Example 3, without the addition of tridecafluorooctyltrimethoxysilane, showed a decrease in average transmittance to 67.85% and an increase in haze to 29.34%. This result indicates that in the absence of a fluorinated silane coupling agent, the compatibility between the hydroxyl-terminated fluorosilicone oil component and the continuous epoxy resin phase is insufficient, potentially leading to phase separation structures above the visible light scale during curing. Such phase separation structures increase the discontinuous refractive index regions within the adhesive layer, resulting in decreased transmittance and increased haze. For Comparative Example 3, the refractive indices listed in Table 4 are apparent refractive indices, primarily used to illustrate the contribution of the fluorinated component to the low refractive index characteristics, and are not suitable for solely evaluating the optical homogeneity of the material.
[0102] Comparative Example 4 eliminated the first-step temperature control section near 75℃ and directly entered a high-temperature curing environment of 120℃. The average light transmittance of its cured film was 91.53%, and the haze was 12.18%. This result indicates that the low-temperature pre-reaction stage plays a role in the uniform reaction of the curing system and the control of volatile byproducts. When curing is carried out directly at higher temperatures, the viscosity of the system may rise rapidly, affecting the migration, reaction, or fixation processes of low-boiling-point components, thereby increasing the possibility of bubble formation or scattering defects within the adhesive layer.
[0103] In summary, the data in Table 4 show that the combined use of fluorosilane coupling agents, bismaleimide trapping components, and a step-curing process is beneficial for obtaining cured films with low refractive index, high visible light transmittance, and low haze.
[0104] Test Example 5: The experimental steps are as follows: (1) The vacuum degassing sealant liquid prepared in Examples 1 to 4 and Comparative Example 1 but not cured was extracted as test objects.
[0105] (2) The liquid density of each test object was determined by the standard specific gravity bottle method under constant temperature of 25℃. A clean and dry glass specific gravity bottle with known volume was placed on a 0.01 g analytical balance and the mass of the empty bottle was weighed. The sealant liquid to be tested was slowly injected into the specific gravity bottle until the liquid overflowed from the bottle mouth. A glass stopper with capillary holes was inserted to remove internal air bubbles and excess adhesive liquid. The outer wall of the bottle was wiped and weighed. The liquid density of the corresponding sample was calculated based on the mass difference and the volume of the specific gravity bottle.
[0106] (3) Slowly pour each group of sealant liquid into the pre-cleaned polytetrafluoroethylene mold cavity, and place the mold together into a hot air circulating oven for heating and curing according to the curing temperature steps and time parameters recorded in each embodiment and comparative example. After curing is completed and the mold is cooled to room temperature in the oven, the mold is removed to obtain the corresponding solid sample.
[0107] (4) The solid density of the solid sample was determined at 25°C using a hydrostatic balance equipped with a density component. The mass of the solid sample in air and the apparent mass when it was suspended by a thin metal wire and completely submerged in deionized water of known density were recorded. The solid density of each sample was calculated based on Archimedes' principle of buoyancy.
[0108] (5) Substitute the measured liquid density and solid density data into the volume shrinkage rate calculation formula: Volume shrinkage rate = (1 - liquid density / solid density) × 100%; Calculate and record the results. Record the sample mass changes simultaneously before and after curing to confirm that the mass loss of each group of samples during the curing process is less than 0.5%, so as to reduce the impact of mass loss on the density ratio calculation results.
[0109] The experimental results are shown in Table 5.
[0110] Table 5. Test data of density and volume shrinkage rate of each sample before and after curing: According to the data in Table 5, the volume shrinkage rates of Examples 1-4 were 1.87%-2.86%, while the volume shrinkage rate of Comparative Example 1 was 8.30%. Compared with Comparative Example 1, Examples 1-4 exhibited lower curing volume shrinkage rates under the same calculation method.
[0111] Comparative Example 1 uses a combination of 1H,1H,2H,2H-perfluorooctyl acrylate and dicumyl peroxide. Its curing process mainly involves the free radical addition polymerization of the acrylate double bonds. This type of addition polymerization is usually accompanied by a shortening of intermolecular distance and a change in free volume, thus exhibiting a high volume shrinkage rate under the test conditions.
[0112] Examples 1-4 did not employ acrylate free radical chain polymerization as the primary curing pathway. The maleimide double bonds in the system mainly participated in volatile matter capture and network construction via Michael addition. The cured network was primarily formed through the ring-opening polymerization of alicyclic epoxy resins. During the ring-opening process of the epoxy groups, the molecular chain segments unfold, which may, to some extent, mitigate the volume shrinkage caused by the crosslinking reaction. Simultaneously, the systems in these examples contained hydroxyl-terminated polytrifluoropropylmethylsiloxane segments, whose flexible segments may also help reduce the impact of volume changes on the adhesive layer during curing.
[0113] The above results indicate that, under the test conditions, the formulations and curing processes of Examples 1-4 are beneficial in reducing the curing volume shrinkage rate, thereby helping to reduce the interfacial stress generated by the sealant during the curing process.
[0114] Test Example 6: The experimental steps are as follows: (1) The sealant solutions prepared in Examples 1 to 4 and Comparative Example 1 and subjected to vacuum degassing were extracted as test materials. In a cleanroom environment, each group of sealant solutions was uniformly coated onto a polyester release film substrate that had undergone surface antistatic treatment using a micron-level wire bar coater.
[0115] (2) The release film substrate coated with adhesive is horizontally transferred to a programmable temperature oven and heated and cured according to the step temperature parameters corresponding to each formulation. After curing and natural cooling to room temperature, the cured adhesive film is peeled off from the surface of the release film. Ten measurement points are randomly selected on the surface of each adhesive film using a non-contact laser thickness gauge to measure the thickness. Unsupported adhesive films with an average thickness in the range of 50±2 micrometers and a thickness range of less than 1 micrometer are selected as test samples.
[0116] (3) Use a standard circular punch to cut each group of films into circular test pieces with a diameter of 100 mm, ensuring that the edges of the test pieces are flat and avoiding visible cracks or gaps.
[0117] (4) Turn on the water vapor transmission rate tester equipped with an infrared sensor to preheat the system and calibrate the baseline. Load the cut test pieces into the test permeation chamber of the instrument, and set the test conditions on the high humidity side to a temperature of 38°C and a relative humidity of 90% in the test software, and introduce dry high-purity nitrogen gas with a constant flow rate as the carrier gas on the low humidity side.
[0118] (5) Start the test program to allow water vapor molecules to pass through the membrane from the high humidity side to the low humidity side under the action of the concentration gradient, and be carried by dry nitrogen into the infrared sensor for quantitative analysis. The instrument continuously collects the transmission signal until the rate of change of transmission in adjacent test cycles is lower than the instrument's set threshold and a stable permeation state is reached, and the corresponding water vapor transmission rate value is recorded.
[0119] The experimental results are shown in Table 6.
[0120] Table 6. Test data on water vapor transmission rate of cured films in each embodiment and comparative example: According to the data in Table 6, under conditions of similar film thickness, the water vapor transmission rate of Examples 1-4 was 4.11 g / (m²). 2 • 24h) to 5.18g / (m 2 (24h), the water vapor transmission rate of Comparative Example 1 was 12.45 g / (m²). 2 • 24h). Compared with Comparative Example 1, the cured films obtained in Examples 1-4 showed lower water vapor permeability under the test conditions.
[0121] Comparative Example 1 uses a combination of 1H,1H,2H,2H-perfluorooctyl acrylate and dicumyl peroxide. Its curing process mainly involves the free radical addition polymerization of the acrylate double bonds, forming blended structures or limited interpenetrating structures with the epoxy / anhydride components in the system. Due to differences in the curing reaction pathways and rates of the different components, this system may form regions with insufficient compatibility or locally high free volumes during curing, making it easier for water vapor molecules to diffuse along microscopic defects or interfacial regions within the adhesive film.
[0122] In Examples 1-4, the formulation system includes hydroxyl-terminated polytrifluoropropylmethylsiloxane, aluminum acetylacetonate, a bismaleimide scavenger, and an alicyclic epoxy resin component. In the first curing stage, the active methylene group in acetylacetonate undergoes a Michael addition reaction with the maleimide double bond in the bismaleimide scavenger, thereby participating in the in-situ fixation of volatile byproducts and the construction of the network structure. In the second curing stage, the alicyclic epoxy resin further undergoes ring-opening polymerization to form a cured network.
[0123] The curing process described above helps reduce defects within the adhesive film caused by volatile migration or insufficient compatibility, and may improve the continuity and density of the polymer network. Simultaneously, the hydroxyl-terminated polytrifluoropropylmethylsiloxane segments contain fluorinated siloxane structures, which can reduce the surface energy of the material to some extent and increase the resistance to water molecule diffusion within the adhesive film.
[0124] Therefore, the results in Table 6 show that the formulations and stepped curing processes in Examples 1-4 are beneficial for reducing the water vapor permeability of the cured adhesive film, thereby improving its barrier performance as a sealing material for optical chips.
[0125] Test Example 7: The experimental steps are as follows: (1) Uncured defoaming sealant solutions from Examples 1-4 and Comparative Example 1 were taken as test components. A standard optical quartz glass substrate and a bare silicon single-crystal chip substrate were used as bonding objects. Before bonding, the two substrates were placed in an ultrasonic cleaning tank and cleaned with acetone, anhydrous ethanol and deionized water for 15 minutes each. After drying with nitrogen, they were placed in an oxygen plasma cleaner for 3 minutes to activate the substrate surface.
[0126] (2) Apply a measured amount of sealant to the bonding area of the silicon chip substrate and stack the optical quartz glass substrate on it. Apply uniform pressure using a custom-made stainless steel fixture to control the effective overlap area of the two substrates to be 5 mm × 5 mm, and maintain the thickness of the intermediate adhesive layer at 20 micrometers by inserting pre-made polyester gaskets around the substrates. Prepare two batches of test samples of the same specifications for each embodiment and comparative example according to the above method.
[0127] (3) Place the assembled test sample along with the tooling fixture into a hot air circulating oven and perform the thermosetting procedure according to the temperature gradient set for each formula. After curing is complete and the sample cools in the oven, remove the tooling to obtain the bonded test component.
[0128] (4) Take the first batch of test samples, fix them on the upper and lower clamps of the universal testing machine, and perform tensile shear test at a constant displacement rate of 2 mm / min. Record the maximum shear force when the interface of the sample is damaged or the adhesive layer is broken, and calculate the initial shear strength by the ratio of the maximum shear force to the effective overlap area.
[0129] (5) Take the second batch of test samples and put them into the thermal shock test chamber for environmental aging test. Set the low temperature range to -40℃, the high temperature range to 125℃, the residence time under extreme temperature environment to 30 minutes, the high and low temperature transition time to 3 minutes, and perform 500 thermal shock cycles continuously.
[0130] (6) Remove the aged samples after thermal shock cycling and allow them to stand at room temperature for 24 hours to reduce the impact of the temperature recovery process before testing on the test results. Then, use a universal testing machine to determine the shear strength after aging. Calculate the shear strength attenuation rate of the corresponding sample according to the following formula: Shear strength attenuation rate = (initial shear strength - shear strength after aging) / initial shear strength × 100%.
[0131] The experimental results are shown in Table 7.
[0132] Table 7. Shear strength and attenuation rate test data of each sample before and after thermal shock: According to the data in Table 7, the initial shear strength of Examples 1-4 was 17.82 MPa to 19.04 MPa. After 500 cycles of thermal shock from -40°C to 125°C, the shear strength after aging was 16.51 MPa to 18.12 MPa, with a shear strength attenuation rate of 4.83% to 7.35%. The initial shear strength of Comparative Example 1 was 16.42 MPa, and after aging, the shear strength decreased to 8.65 MPa, with a shear strength attenuation rate of 47.32%. Compared with Comparative Example 1, Examples 1-4 exhibited a higher shear strength retention rate after thermal shock.
[0133] Comparative Example 1 uses a combination of 1H,1H,2H,2H-perfluorooctyl acrylate and dicumyl peroxide. Its curing process mainly involves the free radical addition polymerization of the acrylate double bonds, accompanied by the curing or physical intercalation of the epoxy / anhydride components under heating conditions. Combined with the volume shrinkage results of Test Example 5, this system may experience relatively high volume shrinkage during curing, resulting in residual stress near the adhesive layer or bonding interface. During thermal shock, there are differences in thermal expansion behavior between the silicon chip, quartz glass, and the cured adhesive layer. The superposition of the aforementioned thermal stress and the residual stress after curing may promote the expansion of local defects at the bonding interface, leading to a decrease in the effective load-bearing area and a significant reduction in shear strength after aging.
[0134] Examples 1-4 did not employ acrylate free radical chain polymerization as the primary curing pathway. Instead, the cured network was mainly formed through the ring-opening polymerization of alicyclic epoxy resins, with bismaleimide scavengers participating in the network structure construction. This curing method helps reduce interfacial stress caused by volume shrinkage during curing. Simultaneously, the fluorinated alkyltrimethoxysilane coupling agent in the example systems can undergo a condensation reaction with the hydroxyl groups on the silicon / glass substrate surface after the hydrolysis of its terminal methoxy groups, forming Si-O-Si interfacial bonding structures, which together with the organic cured network constitute the adhesive interface.
[0135] The above results indicate that, under the test conditions, the formulations and stepped curing processes of Examples 1-4 are beneficial to improving the shear strength retention rate of the silicon chip / quartz glass bonding structure after thermal shock, thereby improving the interfacial stability of the sealant under temperature cycling conditions.
[0136] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A low-refractive-index high-performance sealant for AR / VR glasses chips, characterized in that, The sealant is made from raw materials comprising the following parts by weight: 35-45 parts of alicyclic epoxy resin; wherein the alicyclic epoxy resin is 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate or bis(3,4-epoxycyclohexylmethyl)adipate. 5-12 parts of acid anhydride curing agent; 1-3 parts of fluorinated alkyltrimethoxysilane; wherein the fluorinated alkyltrimethoxysilane is tridecylfluorooctyltrimethoxysilane or heptadecafluorodecyltrimethoxysilane; 40-50 parts of hydroxyl-terminated polytrifluoropropylmethylsiloxane; Aluminum acetylacetone 1.5–3 parts; 3 to 6 parts of a bismaleimide compound; wherein the bismaleimide compound is N,N'-m-phenylenebismaleimide or 4,4'-diphenylmethanebismaleimide.
2. The low-refractive-index high-performance sealant for AR / VR glasses chips according to claim 1, characterized in that, The sealant is made from raw materials comprising the following parts by weight: 40 parts of alicyclic epoxy resin; 8 parts of acid anhydride curing agent; 1 part of fluorinated alkyltrimethoxysilane; 45 parts of hydroxyl-terminated polytrifluoropropylmethylsiloxane; 2 parts of aluminum acetylacetonate; Four portions of bismaleimide compounds.
3. The low-refractive-index high-performance sealant for AR / VR glasses chips according to claim 1, characterized in that, The anhydride curing agent is methylhexahydrophthalic anhydride or hexahydrophthalic anhydride.
4. The low-refractive-index high-performance sealant for AR / VR glasses chips according to claim 1, characterized in that, The hydroxyl-terminated polytrifluoropropylmethylsiloxane has a dynamic viscosity of 1100–2900 mPa·s at 25°C.
5. The low-refractive-index high-performance sealant for AR / VR glasses chips according to claim 4, characterized in that, The hydroxyl-terminated polytrifluoropropylmethylsiloxane is prepared by the following steps: Under inert gas protection, the monomer of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane is heated to 80-100°C, tetramethylammonium hydroxide and deionized water are added, and the reaction is carried out by ring-opening polymerization with stirring at 80-100°C for 3-6 hours. Then, the temperature is raised to 140-160°C and held for 1.5-2.5 hours to decompose and volatilize the catalyst tetramethylammonium hydroxide. Subsequently, under vacuum conditions of -0.090 to -0.098 MPa, the low molecular weight cyclic oligomers are removed at 140-160°C, and the mixture is cooled to room temperature to obtain the final product.
6. The low-refractive-index high-performance sealant for AR / VR glasses chips according to claim 5, characterized in that, The material ratio used to prepare the terminal hydroxyl polytrifluoropropylmethylsiloxane is as follows: 100 parts by weight of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane monomer, combined with 0.05-0.08 parts by weight of tetramethylammonium hydroxide and 0.05-0.12 parts by weight of deionized water.
7. A method for preparing a low-refractive-index high-performance sealant for AR / VR glasses chips as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Under conditions of 20-25°C and relative humidity below 30%, the alicyclic epoxy resin and the acid anhydride curing agent are added to a mixer, and then the fluorinated alkyl trimethoxysilane is added dropwise. The dispersion disc is started to stir, and a basic homogeneous epoxy liquid is obtained. S2. Add the terminal hydroxyl polytrifluoropropylmethylsiloxane to the basic homogeneous epoxy liquid obtained in S1, adjust the stirrer to high shear emulsification mode, and set the speed to 1500-2000 rpm. While dispersing under high shear, add the aluminum acetylacetonate and the bismaleimide compound in the form of solid powder in batches at a uniform speed, and continue high shear dispersion for 40-50 minutes. S3. Seal the mixer and turn on the vacuum system. Switch the mixing mode to low-speed anchor scraping wall mixing for degassing treatment. The speed of the low-speed anchor scraping wall mixing is set to 30-50 rpm, and the degassing treatment time is 30-45 minutes to obtain the degassed sealant.
8. The preparation method according to claim 7, characterized in that, In step S1, the stirring speed of the dispersion disc is set to 400-600 rpm, and the stirring time is 15-25 minutes.
9. The preparation method according to claim 7, characterized in that, The aluminum acetylacetonate and the bismaleimide compound powder were added in 3 to 5 portions at a uniform rate.
10. The preparation method according to claim 7, characterized in that, In step S3, the vacuum system evacuates the machine to a gauge pressure of -0.090 to -0.098 MPa.
Citation Information
Patent Citations
High-adhesion underfill adhesive, preparation method thereof and chip packaging structure
CN121046009A
Solvent-resistant waterproof sealant for AR / VR glasses and preparation method thereof
CN121379466A